Prospect of Stem Cells as Promising Therapy for Brachial Plexus Injury: A Systematic Review - Sumarwoto, Tito; Suroto, Heri; Mahyudin, Ferdiansyah; Utomo, Dwikora Novembri; Romaniyanto, FNU; Prijosedjati, Andhi; Notobroto, Hari Basuki; Tinduh, Damayanti; Prakoeswa, Cita Rosita Sigit; Rantam, Fedik Abdul; Rhatomy, Sholahuddin (Taylor & Francis, 2022)
Background: Brachial plexus injury is an advanced and devastating neurological injury, for which both nerve surgery and tendon transfers sometimes remain insufficient in restoring normal movement. Stem cell therapy may be applicable to rescue the injured motor neurons from degeneration which potentially improves muscle strength. Study Design: Systematic Review; Level of evidence V. Data Sources: A systematic literature search was conducted on PubMed (MEDLINE), EMBASE, the Cochrane Library, and Scopus using the terms (“stem cell”) AND (“brachial plexus”) as search keywords. Methods: The process of study selection was summarized by PRISMA flow diagram. The study included in vivo and in vitro studies with English language, humans or animals with some brachial plexus injuries, interventions, some applications of stem cells to the groups of study, with functional, biomechanical, or safety outcomes. Results: In total, there were 199 studies identified from the literature sources where 75 articles were qualified for forward evaluation following selecting the titles and abstracts. Ten studies were finally included in this systematic review after full-text assessment. Stem cells can produce neurotrophic factors in vitro and in vivo in rats, and their level was increased after injury. Electrophysiological measurement showed that the intervention group had distinctly higher CMAP amplitude and evidently shorter CMAP latency than the model group. Application of bone marrow stem cells (BMSCs) showed an elevation in the numbers of axons and density of myelinated fibers, the density of nerve fibers, the diameter of regenerating axons, and a decrease in axonal degeneration. A study in humans indicated an improvement of the movements in a patient with traumatic total BPI after injection of Ad-MSC. It is associated with increased muscle mass and sensory recovery and also suggested that mononuclear cell injection enhances muscle regeneration and reinnervation in the partly denervated muscle of brachial plexus injury. Various muscle groups had obtained strength together with restoration, the muscle strength attained after the previous transplantation were preserved. The results of this review support stem cell treatment in brachial plexus injury. Conclusion: This review provides evidence of the positive effects of stem cell treatment in brachial plexus injury.